You may identify two methods of checking if the statement is true, at least. One method is described in previous answer, hence you may also use the alternative method to do the verification.
You may also open the brackets both sides and then you should compare the results such that:
`2x + 2 + xy + y = 2x + 2 + xy + y`
Notice that you also may find the terms from the left side to the right side, hence the given statement is true.
Yes this is correct.
To work out the answer easily all you need to do is multiply out all of the brakets and you can clearly see that both sides equal the same thing.
Hope that helps!!!
It is true.
We can take `(x+1)` factor out as below,
Therefore `LHS=RHS` .
And the statement is true.
The statement 2(x + 1) + y(x + 1) = (2 + y)(x + 1) is true
L.H.S = 2(x + 1) + y(x + 1) = 2x + 2 + xy + y
R.H.S = (2 + y)(x + 1) = 2x + 2 + xy + y
Since L.H.S = R.H.S
Hence the statement 2(x+1)+y(x+1)=(2+y)(x+1) is true